1987
DOI: 10.1002/maco.19870380910
|View full text |Cite
|
Sign up to set email alerts
|

The development of silicon‐containing oxides during the oxidation of iron‐chromium‐base alloys

Abstract: The influence of silicon on the oxidation of Fe‐14% Cr and Fe‐28% Cr has been studied at high temperature, with particular emphasis on the development and nature of the healing SiO2 layer. In general, silicon is a less effective addition than aluminium to these alloys in improving oxidation resistance because SiO2 grows at a lower rate than α‐Al2O3. Hence, silicon is a less successful oxygen secondary getter and development of a complete healing layer of SiO2 is less rapid than that of α‐Al2O3 on a correspondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 25 publications
3
30
1
Order By: Relevance
“…the AES results discussed above) is fully amorphous (in accordance with results reported in Ref. 22). …”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…the AES results discussed above) is fully amorphous (in accordance with results reported in Ref. 22). …”
Section: Resultssupporting
confidence: 79%
“…Although small additions of Si to Cr 2 O 3 -scale-forming steel are known to improve its high-temperature corrosion resistance (in particular, it enhances the reformation of a protective Cr 2 O 3 scale on the barealloy surface after oxide spallation [3,10,[12][13][14][15]), a fundamental understanding of this effect lacks [15][16][17][18]. The Si content corresponding with the maximum oxidation resistance (i.e., the longest breakaway oxidation time at constant temperature) appears to depend strongly on the steel microstructure [3,10,13,[19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…An amorphous silica layer, which was believed to act as a diffusion barrier to reduce iloxidation rates, has been detected [20][21][22] at oxide/alloy interfaces in alloys con_ning Si, and the presence of such a silica layer also increased scale spallation [21]. In the present study, the silica layer was never found to be continuous.…”
Section: Oxide Morphology and Compositi0ncontrasting
confidence: 38%
“…The former was inferred to be SiO 2 . Addition of Si is known to improve the oxidation resistance of chromia-forming alloys [10][11][12]; however, it is also known to decrease scale spallation resistance [12][13][14]. Apparently, the nominally 2.75 wt% Si addition in the HR-160 alloy forms a continuous SiO 2 layer at the chromia/alloy interface and this in turn may have considerably decreased scale adhesion particularly at 982 o C. It is seen from Table III that HR-160 alloy underwent considerable metal loss (~ 43 µm) at 982 o C even though it contains sufficient amount of Cr to establish a protective oxide scale.…”
Section: Resultsmentioning
confidence: 99%